2004
DOI: 10.1088/0266-5611/20/3/017
|View full text |Cite
|
Sign up to set email alerts
|

Minimum support nonlinear parametrization in the solution of a 3D magnetotelluric inverse problem

Abstract: In this paper we describe a new approach to shar p boundary geophy sical inversion. We demon strate that regularized inversion with a minimum support stabilizer can be implemented by using a specially designed nonl inear parametrization of the mode l parameters. Thi s parametrization plays the same role as transformation into the space of the weighted model parameters, introd uced in the origi nal papers on focusing inversion. It allows us to transform the nonq uadrati c minim um support stabilizer into the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 16 publications
0
67
0
Order By: Relevance
“…It is also planned to apply our inversion scheme to an experimental data set. However, previous examples from other 3-D MT inversion software developers (see [8,10,14,17]) indicate that successful verification of the inversion technique even on a single practical dataset is a complex task and may take some time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also planned to apply our inversion scheme to an experimental data set. However, previous examples from other 3-D MT inversion software developers (see [8,10,14,17]) indicate that successful verification of the inversion technique even on a single practical dataset is a complex task and may take some time.…”
Section: Resultsmentioning
confidence: 99%
“…This example includes a tilted conductive dyke in a uniform half-space (see [17]). The results presented are encouraging and suggest that the inversion may be successfully applied to solving realistic 3-D inverse problems with real MT data.…”
Section: Introductionmentioning
confidence: 99%
“…The original work of Last and Kubik [1983] suggests that β should have a value close to machine precision (≈ 10 −11 in their case) with λ determined using the discrepancy principle and an assumed, although somewhat arbitrary, noise level. Zhdanov and Tolstaya [2004] advocates the use of a procedure similar to the L-curve technique where β is chosen to be the point of maximum curvature on the trade-off curve relating β to A(m). We have observed that setting β to values near machine precision results in severe instability and that the approach of Zhdanov and Tolstaya [2004] often yields trade-off curves with poorly defined corners.…”
Section: Misfit Levels (λ β) Selection and Convergence Testsmentioning
confidence: 99%
“…Zhdanov and Tolstaya [2004] advocates the use of a procedure similar to the L-curve technique where β is chosen to be the point of maximum curvature on the trade-off curve relating β to A(m). We have observed that setting β to values near machine precision results in severe instability and that the approach of Zhdanov and Tolstaya [2004] often yields trade-off curves with poorly defined corners. We therefore fix β at a reasonable value determined by experience, typically between 10 −4 and 10 −7 .…”
Section: Misfit Levels (λ β) Selection and Convergence Testsmentioning
confidence: 99%
“…The resistivity map is then varied iteratively to minimize the objective function, thus giving a trade-off between fitting the data and the assumed nonoscillatory nature of the solution. (Some recent developments in regularization theory have dealt with sharp geoelectric boundaries; see [13], [3], [15].) Paradoxically, it is well known that resistivity does not vary smoothly with depth, but has order one oscillations on very small spatial scales.…”
mentioning
confidence: 99%